2019
DOI: 10.1038/s41598-019-43535-6
|View full text |Cite
|
Sign up to set email alerts
|

Aminophospholipids are signal-transducing TREM2 ligands on apoptotic cells

Abstract: Variants of triggering receptor expressed on myeloid cells 2 (TREM2) are associated with an increased incidence of Alzheimer’s disease, as well as other neurodegenerative disorders. Using a newly developed, highly sensitive reporter cell model, consisting of Jurkat T cells stably overexpressing a reporter gene and a gene encoding TREM2DAP12 fusion protein, we show here that TREM2-dependent signal transduction in response to apoptotic Neuro2a cells is mediated by aminophospholipid ligands, phosphatidylserine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 65 publications
2
65
0
Order By: Relevance
“…This revealed a dose-dependent increase in p-SYK upon addition of 4D9 but not 4D9 Fab to the culture media of the cells ( Fig 2D). Furthermore, anionic liposome ligand (Shirotani et al, 2019) stimulated TREM2 signaling 2.3-fold by fulllength 4D9 but not by 4D9 Fab or the isotype control ( Fig 2E). These data therefore suggest that the monoclonal antibody 4D9 enhances TREM2-dependent signaling via bivalent binding which cross-links TREM2 on the plasma membrane.…”
Section: Screening and Molecular Characterization Of Anti-trem2 Antibmentioning
confidence: 92%
“…This revealed a dose-dependent increase in p-SYK upon addition of 4D9 but not 4D9 Fab to the culture media of the cells ( Fig 2D). Furthermore, anionic liposome ligand (Shirotani et al, 2019) stimulated TREM2 signaling 2.3-fold by fulllength 4D9 but not by 4D9 Fab or the isotype control ( Fig 2E). These data therefore suggest that the monoclonal antibody 4D9 enhances TREM2-dependent signaling via bivalent binding which cross-links TREM2 on the plasma membrane.…”
Section: Screening and Molecular Characterization Of Anti-trem2 Antibmentioning
confidence: 92%
“…Numerous phagocytic receptors involved in the recognition of exposed PS (either directly or through adapter proteins such as Gas6) are expressed by microglia and astrocytes, including TREM2, MerTK, Axl, Tyro3, and Bai1 (Chung et al, 2013;Fadok et al, 2001;Graham et al, 2014;Grommes et al, 2008;Nakano et al, 1997;Neher et al, 2012;Park et al, 2007;Païdassi et al, 2008;Shirotani et al, 2019). Further, several of these receptors have been implicated in synaptic elimination by glia (Chung et al, 2013;Filipello, Morini et al, 2018).…”
Section: Mechanisms Of Glial Synaptic Pruning Converge On Ps As a Commentioning
confidence: 99%
“…For example, in Drosophila, it has recently been demonstrated that PS exposure can occur locally on injured dendrites, which are then targeted for elimination while sparing the remaining uninjured cell structures (Sapar et al, 2018). The recognition of exposed PS by phagocytes, a process that is critical in the clearance of apoptotic cells and debris to prevent autoimmunity, is facilitated by numerous phagocytic receptors including microglial TREM2 (Graham et al, 2014;Grommes et al, 2008;Park et al, 2007;Shirotani et al, 2019). Further, complement binding to exposed PS, either directly or indirectly, can mediate engulfment in the periphery (Martin et al, 2012;Païdassi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…do not grossly impact protein structure or stability but instead likely disrupt interactions with important ligands [15,16]. Several proteins and biological compounds have been demonstrated to bind TREM2 [17], and AD-relevant ligands such as apoptotic cells [18], phospholipids [18,19], low-and high-density lipoprotein [20,21], apolipoprotein E (ApoE) [22], and oligomeric Aβ [23][24][25] have been confirmed to induce TREM2-mediated signaling or phagocytosis. Given the multiple ligands mediating the various functions associated with TREM2, it is important to understand how TREM2 engages each of these ligands at the molecular level.…”
Section: Introductionmentioning
confidence: 99%